Low Pretreatment Albumin-to-Globulin Ratio Predicts Poor Prognosis in Gastric Cancer: Insight From a Meta-Analysis - Wei, Chengzhi; Yu, Zhu; Wang, Gonghe; Zhou, Yiming; Tian, Lei (Frontiers in Oncology, 2021)
Background: In recent five years, reports regarding albumin-to-globulin ratio (AGR) and the survival of gastric cancer (GC) have emerged rapidly, yet their association remains controversial. This meta-analysis was aimed to provide an insight into the prognostic significance of pretreatment AGR in GC. Methods: PubMed, Embase, Cochrane library, Web of Science, WanFang, China National Knowledge Infrastructure (CNKI) and VIP databases were searched for relevant studies, from inception to September 30, 2020. Individual hazard ratios (HRs) with their 95% confidence intervals (CIs) were combined by Stata 12.0 software to evaluate the association between pretreatment AGR and overall survival (OS) and disease-free survival/progression-free survival (DFS/PFS). Results: A total of 8,305 patients with GC from 12 studies were included for further analysis. Pooled analyses indicated that low AGR was closely associated with worse OS (HR = 1.531, 95% CI: 1.300-1.803, P < 0.001) and worse DFS/PFS (HR = 2.008, 95% CI: 1.162-3.470, P = 0.012) in GC patients. Moreover, subgroup analyses demonstrated that the association between low AGR and worse OS remained constant despite variations in country, tumor stage, cut-off value, cut-off selection and treatment method. Conclusion: AGR could act as an efficient prognostic indicator for GC, and that low pretreatment AGR predicts poor prognosis in GC.